ISOLASI, KARAKTERISASI, DAN PATOGENITAS BAKTERI PENYEBAB PENYAKIT PADA GURAMI (Osphronemus goramy) DI KABUPATEN BANTUL - Murwantoko Murwantoko; Rozi Rozi; Indah Istiqomah; Kamiso H. Nitimulyo (Jurnal Perikanan Universitas Gadjah Mada, 2013)
Gouramy (Osphronemusgoramy) is an important ﬁsh comodity and preferred to be consumed by people. One of the limiting factor in freshwater aquaculture is bacterial infections. The objective of this research was to identify the species of pathogenic bacteria on gourami from Bantul Regency and to determine their pathogenicity. Eighteen diseased gouramy were collected from seven different ﬁ sh farms. Bacteria were isolated from kidney and purifyon TSA medium. Characterization was conducted on the morphology of bacterial colonies and cells, biochemical tests. Koch Postulate Test was done to conﬁrm pathogenic properties of the isolated bacteria. Pathogenicity test was performed by intraperitoneal injection of a serial doses of bacteria into gouramy and the Lethal Dosage 50 (LD50) was calculated. Twenty isolates of Aeromonas hydrophila, 5 isolates of Aeromonas salmonicida and one isolate of Vibrio cholerae,Vibrio anguillarum and Pseudomonas ﬂuorescens respectively were isolated from and conﬁ rmed as pathogen ingouramy. Pathogenic diversity was found among isolated bacteria, which a group of virulent bacteria as Aeromonas hydrophila GBNB, GGRB, and GCMA3 with LD50 values of 6.28 x 105, 2.09 x 105 and 5.37 x 105 CFU /ﬁsh; and a group of non virulent bacteria as A. hydrophila GKRA isolate and Vibrio cholera GPDA isolat with LD50 value of 7.14 x 107 and 3.45 x 107 CFU/ﬁsh respectively.